2015
DOI: 10.1115/1.4031765
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Effect of Head Acceleration on Brain Responses to Blast Waves

Abstract: Multiple injury-causing mechanisms, such as wave propagation, skull flexure, cavitation, and head acceleration, have been proposed to explain blast-induced traumatic brain injury (bTBI). An accurate, quantitative description of the individual contribution of each of these mechanisms may be necessary to develop preventive strategies against bTBI. However, to date, despite numerous experimental and computational studies of bTBI, this question remains elusive. In this study, using a two-dimensional (2D) rat head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Although the maximum reflected pressure occurred at the eye socket in the front-on case, the relatively small area interacted with the blast wave resulted in minimal ICP in this case. The computational work by Mao et al [17] demonstrated a similar trend in the rat brain, i.e., higher pressure for a lateral blast loading compared to a frontal one. However, the experimental work by Chavko et al [10] showed that rats experienced higher brain pressure in the frontal loading compared to that in the side-on one.…”
Section: Discussionmentioning
confidence: 77%
“…Although the maximum reflected pressure occurred at the eye socket in the front-on case, the relatively small area interacted with the blast wave resulted in minimal ICP in this case. The computational work by Mao et al [17] demonstrated a similar trend in the rat brain, i.e., higher pressure for a lateral blast loading compared to a frontal one. However, the experimental work by Chavko et al [10] showed that rats experienced higher brain pressure in the frontal loading compared to that in the side-on one.…”
Section: Discussionmentioning
confidence: 77%
“…We developed a 3-D FE model of a partial shock tube, similar to previous models,13,19,20 with a square cross-section of 0.20 m in width and 1.25 m in length (Fig. 1c).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, extension to large deformations under visco‐hyperelastic constitutive laws, frequency dependent material properties, and multiscale approaches will then allow to investigate a wider range of frequencies, as well as the biomechanics of impact and traumatic brain injury phenomena, edema and deep subdural hematoma, and glioblastoma tumor growth . In this perspective, the high heterogeneity of the material model and the complexity of the geometry domain do not allow an easy prediction of the maximum displacement locations; however, the numerical study highlights measurable differences in the different regions.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, advances in constitutive and computational tools of soft tissue biomechanicss allowed to address head bone conduction and its characteristic frequencies . Recently, advanced modeling tools have been specifically developed for skull sound‐wave measurement, head‐neck modal analysis, computational models for head injury validation, computer‐based atlas models, and brain biomechanical characterization …”
Section: Introductionmentioning
confidence: 99%